Analysis of The Use of Onshore Power Supply Facility at Port of Berlian - Kustanto, Jaka Septian; Rachman, Natriya Faisal; Nurdiansari, Henna; Gupron, Akhmad Kasan (Journal of Earth and Marine Technology (JEMT), 2024)
Ships contribute to CO2 gas emissions. The government's effort to reduce these emissions is by having Onshore Power Supply (OPS) facilities. OPS is a technology that allows ships at anchor to turn off their engines and connect to the local electricity network for electricity supply. Port of Berlian currently has 8 OPS spot managed by PT. Lamong Energi Indonesia. The use of OPS still needs to be examined using valid methods. In this research, researchers use the assessment methodology that has been used at the port of Lisbon regarding this onshore electricity facility type of port where the ship is docked (mooring vessel). In this methodology, the assessment process carried out includes data gathering and data processing processes. Apart from this process, it is necessary to review the character of the port or terminal that we will examine ships that most often use land-based electricity facilities are ships with a size of 1000-2999 GT. The use of land electricity facilities provides cost efficiency of 78%. This land electricity facility is used by General Cargo and Container type ships. These results indicate that the use of land electricity facilities is still inefficient ( 2.7%) and there is a need for further review of the implementation of existing policies.